Onychoscopy: an observational study in 237 patients from the Kashmir Valley of North India - Yasmeen Jabeen Bhat (Mattioli1885, 2018)
Background: Nail disorders comprise approximately10% of all dermatological conditions. Because diagnosis is not always possible by clinical means alone, additional diagnostic procedures may be required at times. Dermoscopy of nails (onychoscopy) has shown promising results in diagnosing various nail disorders and also avoids time-consuming investigations such as culture and biopsy.